Antibodies to islet cell autoantigens, rotaviruses and/or enteroviruses in cord blood and healthy mothers in relation to the 2010–2011 winter viral seasons in Israel: a pilot study. Issue 6 (25th February 2014) - Shulman, L. M.; Hampe, C. S.; Ben‐Haroush, A.; Perepliotchikov, Y.; Vaziri‐Sani, F.; Israel, S.; Miller, K.; Bin, H.; Kaplan, B.; Laron, Z.
Abstract Aims To determine whether antivirus and/or islet cell antibodies can be detected in healthy pregnant mothers without diabetes and/or their offspring at birth in two winter viral seasons. Methods Maternal and cord blood sera from 107 healthy pregnant women were tested for islet cell autoantibodies using radioligand binding assays and for anti‐rotavirus and anti‐CoxB3 antibody using an enzyme‐linked immunosorbent assay. Results Glutamic acid decarboxylase (GAD)65 autoantibodies and rotavirus antibodies, present in both maternal and cord blood sera, correlated with an odds ratio of 6.89 (95% CI: 1.01–46.78). For five, 22 and 17 pregnancies, antibodies to GAD65, rotavirus and CoxB3, respectively, were detected in cord blood only and not in the corresponding maternal serum. In 10 pregnancies, rotavirus antibody titres in the cord blood exceeded those in the corresponding maternal serum by 2.5–5‐fold. Increased antibody titres after the 20th week of gestation suggested CoxB3 infection in one of the 20 pregnancies and rotavirus in another. Conclusion The concurrent presence of GAD65 antibodies in cord blood and their mothers may indicate autoimmune damage to islet cells during gestation, possibly caused by cross‐placental transmission of viral infections and/or antivirus antibodies. Cord blood antibody titres that exceed those of the corresponding maternal sample by >2.5‐fold, or antibody‐positive cord blood samples with antibody‐negative maternal samples, may imply an active in utero immune response by the fetus.